Radio What's New? Someone Still Loves You: The Impact of Listening to Prison Radio - Einat, Tomer (The prison journal, 2023)
This study examines the impact of listening to prison radio on the well-being of inmates. Its main quantitative findings are that listening to the radio had no significant impact on inmates’ anxiety, anger, emotional distress, or self-esteem. The qualitative results found that listening to the radio has a positive impact on inmates’ well-being, their outlook, the atmosphere of the prison, and peer relationships. We conclude that the practice of prison radio reflects sophisticated prison administration, reducing feelings of hostility and anger on the part of the inmates and promoting trust among inmates and between them and the staff.